A comparison of Forbush Decreases driven by ICMEs and SIRs - Gutierrez, C.; Dasso, S.; Démoulin, P.; Janvier, M. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)
International audience Solar wind structures passing Earth can shield Earth from Galactic Cosmic Rays (GCRs), producing variations in the GCR flux that can be observed by ground-based detectors. In this paper we study the differences of Forbush decreases (FDs) produced by Interplanetary Coronal Mass Ejections (ICMEs) and Stream Interaction Regions (SIRs), applying a superposed epoch technique to large samples of FDs associated with ICMEs and SIRs. The analysis of the GCRs flux is made using data from neutron monitors at an Antarctic station (McMurdo). We also study the dependence of the FD properties with the bulk velocity of ICMEs/SIRs. We confirm that the faster ICMEs cause the largest FDs. In contrast, the FD intensity in SIRs is weakly dependent of the bulk velocity. Indeed, we find that ICMEs and SIRs with similar solar wind velocity produce very different FDs. This points for a dominant role of the magnetic field in screening GCRs. Finally, we find that in ICMEs the minimum GCR flux is usually observed close to the beginning of the magnetic ejecta, while in SIRs this is usually at the trailing edge.